Technocratic Planning Of Character Education Policy For Indonesian Islamic Values - Dwi Fitri Wiyono (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
Abstract The purpose of the research was to find the concept and formulation of technocratic planning policy on character education of Indonesian Islamic values. This research method uses a qualitative approach, data collection process using literature review and official documents. The results of this study found the integration of the concept of Indonesian Islamic values in the formulation of technocratic planning policy on character education of Indonesian Islamic values, through policy design that begins with the analysis of macro and micro context of character education, integration of Islamic values with the framework of mission vision and priority stages of nation character development, target choice and control of strategies of Indonesian Islamic values in the regional structure and curriculum of Islamic education units. Keywords: Technocratic planning, Islamic education policy, The Character of Indonesian Islam